a1 = -4, means the first term of the sequaence = -4
In the arithmetic sequence, there is a common difference between each two consecutive terms
We can find this difference from the given rule
an = a n-1 + 11
an-1 is the previous term of an
11 is the common difference
The rule of the sequence is
![a_n=a+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/t99kk5roieipg56xa37yseewl9ybc4zh6i.png)
a is the first term
d is the common difference
n is the position of the term
Substitute a by -4
d by 11
![a_n=-4+(n-1)11](https://img.qammunity.org/2023/formulas/mathematics/college/9y2lrh9082tp5v9jqdihjdxtay5v5pmlsb.png)
Multiply the bracket by 11
![\begin{gathered} a_n=-4+n(11)-1(11)_{} \\ a_n=-4+11n-11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y3o1zxr3xu1qf4ipgwhqzzajs2dwpcka6y.png)
Add the like terms -4 and -11
![a_n=11n-15](https://img.qammunity.org/2023/formulas/mathematics/college/iutxhn42wz5a4crvd48jzjhlcz9tpbz3oj.png)
The rule of the sequence is a(n) = 11n - 15